Peripheral nerve lengthening as a regenerative strategy - Vaz, Kenneth M. (Medknow Publications & Media Pvt Ltd, 2014)
Peripheral nerve injury impairs motor, sensory, and autonomic function, incurring substantial financial costs and diminished quality of life. For large nerve gaps, proximal lesions, or chronic nerve injury, the prognosis for recovery is particularly poor, even with autografts, the current gold standard for treating small to moderate nerve gaps. In vivo elongation of intact proximal stumps towards the injured distal stumps of severed peripheral nerves may offer a promising new strategy to treat nerve injury. This review describes several nerve lengthening strategies, including a novel internal fixator device that enables rapid and distal reconnection of proximal and distal nerve stumps.